Strategi Personal Branding Mahasiswa sebagai Modal Awal Memulai Bisnis di Era Ekonomi Kreatif - Fahri Azizi; Muhammad Ridho; Yulia Novita; Zetri Rahmat (CV Muara Edukasi, 2025)
The development of the creative economy in Indonesia demands that the younger generation, particularly university students, possess entrepreneurial skills that rely not only on technical skills but also on the ability to build a self-image, or personal branding. Personal branding is a crucial instrument for creating differentiation, strengthening consumer trust, and increasing competitiveness in the early stages of starting a business. This study aims to analyze students' personal branding strategies as initial capital for starting a business in the creative economy ecosystem, identify the elements that shape personal brand credibility, and explain the role of digital platforms in constructing students' professional identities. This research used a qualitative descriptive method through literature review and limited interviews with student entrepreneurs in the culinary, fashion, creative services, and digital content sectors. The results indicate that strong personal branding is built through consistent values, authenticity, structured visual communication, and the use of digital media as a space for self-representation. Personal branding has been shown to increase student entrepreneurs' visibility, accelerate the development of consumer trust, and increase interest in collaboration. These findings confirm that personal branding is a fundamental asset that young entrepreneurs need to compete and survive in the creative industry